Pengembangan Kawasan Pelabuhan Perikanan Pantai Carocok Tarusan Di Pesisir Selatan Dengan Pendekatan Arsitektur Tepian Air - Utama, Windri Hadi; Hidayat, Wahyu; Susilawati, Mira Dharma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Fisheries port of Carocok Tarusan Beach in Pesisir Selatan is stipulated in RTRW of Pesisir Selatan Regency as a tourism port. However, it has not been able to show as a tourism port. So, it takes the development of the area to become a tourism port area. The design method used is the result of field surveys, documentation, analysis of qualitative data and quantitative data. The development utilizes the existing port and the area of land around the port. So that the result of the development will be mutually integrated between the fisheries port and the area for tourism and fisheries activities. The design theme uses the theme of water edge architecture whose main principle is to utlize the physical and visual potential, namely the mangrove protected area, so the concept used in this development is identity of mangrove, making the reference to area development referring to the principle of life of mangrove plants. The result of the develoment divide the zone of the area into fisheries port zones, socio-cultural zones, and recreation zones. Development is expected to be able to accommodate fishing port actvities and tourism activities in tandem..Keyword: Pesisir Selatan, Fisheries Port , Waterfront Architecture.